Poetic Justice: Corruption in Lambton County, Canada West, 1854-1858 - Stott, Gregory (Ontario History)

(untitled) (The Ontario Historical Society, 2013)
Beginning in 1855 Lambton County merchant, postmaster, poet, Orangeman and moderate conservative Robert McBride (1811-1895) saw himself as a victim of a conspiracy launched by scheming Reform-minded politicians and their cronies. In books of poetry, particularly his hefty Poems Sentimental & Satirical On Many Subjects Connected with Canada, and drawing on his own experiences, he outlined the malfeasance of the judiciary, the ‘land jobbing’ class, and others associated with the Reform movement in Canada West who, he claimed, were undermining and corrupting the British foundations of the province. McBride’s poetry and other contemporary documentation about his legal travails help us understand the complex connections that existed among colonial administrators at the local level in Canada West in the 1850s.